Sexual identities and sexual health within the Celtic nations: An exploratory study of men who have sex with men recruited through social media. Issue 7 (13th September 2016) - McAloney-Kocaman, Kareena; Lorimer, Karen; Flowers, Paul; Davis, Mark; Knussen, Christina; Frankis, Jamie
ABSTRACT: Associations of sexual identity with a range of sexual and sexual health behaviours were investigated amongst men who have sex with men (MSM). Data from 1816 MSM recruited from 4 Celtic nations (Scotland, Wales, Northern Ireland and the Republic of Ireland) were collected via a cross-sectional online survey advertised via social media. About 18.3% were non-gay identified MSM (NGI-MSM). In the last year, 30% of NGI-MSM reported high-risk unprotected anal intercourse and 45% reported never having had an sexually transmitted infection (STI) test. When compared to MSM who were gay identified (GI-MSM), NGI-MSM were more likely to be older, have a female partner, fewer sex partners, fewer anal sex partners, STI diagnoses and less likely to be HIV positive, more likely to never use the gay scene and be geographically further from a gay venue. NGI-MSM were also less likely to report STI and HIV testing behaviours. The findings highlight variations in risk by sexual identities, and unmet sexual health needs amongst NGI-MSM across Celtic nations. Innovative research is required regarding the utility of social media for reaching populations of MSM and developing interventions which target the heterogeneity of MSM and their specific sexual health needs.